Implementasi Manajemen dan Digitalisasi Perpustakaan di SDN Rungkut Menanggal I Surabaya - Shinta Nurhalizah; Rashel Dea Astiavi Rosita; Ifrochaini Al Mazidah; Din Arsy Anindita Kirana; Moh. Edwin Dwi Ghazali; Hafiz Adrian Dinata; Iga Dwi Rianningrum; Rezki Nurma Fitria (Indonesian Journal Publisher, 2025)
Effective and digitally-based school library management plays a crucial role in supporting the learning process and strengthening students' literacy skills. This study aims to investigate the implementation of library management and digitalization at SDN Rungkut Menanggal I Surabaya, focusing on organizational structure, collection classification and cataloging systems, library services, and literacy programs. A descriptive qualitative approach was used, with the research conducted at SDN Rungkut Menanggal I. Data were collected through observation, in-depth interviews with the librarian, and documentation, and then analyzed descriptively. The results show that the library has a complete and functional organizational structure with clearly defined roles. The classification and cataloging process uses the Dewey Decimal Classification (DDC) system, supported by the Inlis Lite 3.2 application, which improves collection management efficiency. The library provides services such as reading rooms, circulation services, and scheduled class visits, all designed to encourage students’ reading habits. Additionally, literacy programs are held regularly and include various activities such as reading books, watching educational videos, and completing summaries or quizzes, all of which have proven to increase students’ reading interest and thinking skills. These findings demonstrate that a well-structured library management system and the integration of technology contribute to creating a more active and enjoyable learning environment in elementary schools.